2018
DOI: 10.1016/j.neuron.2018.07.036
|View full text |Cite
|
Sign up to set email alerts
|

Multi-dimensional Coding by Basolateral Amygdala Neurons

Abstract: Conditioned appetitive and aversive responses (CRs) are thought to result from the activation of specific subsets of valence-coding basolateral amygdala (BLA) neurons. Under this model, the responses of BLA cells to conditioned stimuli (CSs) and the activity that drives CRs are closely related. We tested the strength of this correlation using a task where rats could emit different CRs in response to the same CSs. At odds with this model, the CS responses and CR-related activity of individual BLA cells were sep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
117
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(136 citation statements)
references
References 55 publications
17
117
1
1
Order By: Relevance
“…Our data support an impairment in 2-AG synthesis over changes in degradation, as both 2-AG and free AA levels were reduced and only the maximal magnitude (but not recovery) of DSE was reduced in the PFC ~24h after stress exposure. If increased 2-AG degradation were the primary driver of reduced 2-AG signaling, one would expect elevated levels of AA and a faster DSE decay (Pan et al, 2009;Zhong et al, 2014) The BLA is highly heterogeneous and its distinct roles in the processing of positive and negative valence have been dissected and defined by projection target, gene expression, and electrophysiological characteristics (Beyeler et al, 2018;Kim et al, 2016;Kyriazi et al, 2018;Namburi et al, 2016). Interestingly, putative 'negative valence' and 'positive valence' BLA neurons, as defined by genetic markers, show distinct projections to the mPFC (Kim et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Our data support an impairment in 2-AG synthesis over changes in degradation, as both 2-AG and free AA levels were reduced and only the maximal magnitude (but not recovery) of DSE was reduced in the PFC ~24h after stress exposure. If increased 2-AG degradation were the primary driver of reduced 2-AG signaling, one would expect elevated levels of AA and a faster DSE decay (Pan et al, 2009;Zhong et al, 2014) The BLA is highly heterogeneous and its distinct roles in the processing of positive and negative valence have been dissected and defined by projection target, gene expression, and electrophysiological characteristics (Beyeler et al, 2018;Kim et al, 2016;Kyriazi et al, 2018;Namburi et al, 2016). Interestingly, putative 'negative valence' and 'positive valence' BLA neurons, as defined by genetic markers, show distinct projections to the mPFC (Kim et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The BLA is highly heterogeneous and its distinct roles in the processing of positive and negative valence have been dissected and defined by projection target, gene expression, and electrophysiological characteristics (Beyeler et al, 2018;Kim et al, 2016;Kyriazi et al, 2018;Namburi et al, 2016). Interestingly, putative 'negative valence' and 'positive valence' BLA neurons, as defined by genetic markers, show distinct projections to the mPFC (Kim et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…It has long been recognized that BL neurons are responsive to various types of sensory stimuli, particularly if they have been paired with aversive or rewarding outcomes (for instance see, Uwano, Nishijo, Ono, & Tamura, ). In fact, recent studies have revealed that BL neurons concurrently encode multiple dimensions, including the sensory properties of stimuli, their reward value, contextual information, the hierarchical rank of con‐specifics as well as various behaviors such as freezing, active avoidance, reward approach, and movement speed (Amir, Lee, Headley, Herzallah, & Paré, ; Belova, Paton, & Salzman, ; Kyriazi, Headley, & Paré, ; Munuera, Rigotti, & Salzman, ; Saez, Rigotti, Ostojic, Fusi, & Salzman, ).…”
Section: Discussionmentioning
confidence: 99%